2006
DOI: 10.1002/gps.1487
|View full text |Cite
|
Sign up to set email alerts
|

Do subjective memory complaints predict cognitive dysfunction over time? A six-year follow-up of the Maastricht Aging Study

Abstract: Being forgetful might be an indicator of slower general information processing speed and delayed recall at baseline but does not predict cognitive change over 6 years in older adults. However, the effects are rather small and cannot directly be generalized to applications in clinical settings. Other factors, such as depression and anxiety might also underlie the cause of the forgetfulness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
85
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(98 citation statements)
references
References 39 publications
12
85
0
1
Order By: Relevance
“…Previous research has also shown that subjective memory complaints are frequently caused by psychiatric disorders, most commonly by a depressive disorder, and these patients are often seen in memory clinics (30). Investigating the psychosocial determinants of forgetfulness in persons aged between 53 and 94 (mean age = 72 years), Mol and colleagues (31) found that 'low memory selfefficacy, negative attitude, high memory related anxiety and high subjective norm' (i.e., what others in society think about memory failures) all contributed to a person's perceived forgetfulness.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has also shown that subjective memory complaints are frequently caused by psychiatric disorders, most commonly by a depressive disorder, and these patients are often seen in memory clinics (30). Investigating the psychosocial determinants of forgetfulness in persons aged between 53 and 94 (mean age = 72 years), Mol and colleagues (31) found that 'low memory selfefficacy, negative attitude, high memory related anxiety and high subjective norm' (i.e., what others in society think about memory failures) all contributed to a person's perceived forgetfulness.…”
Section: Discussionmentioning
confidence: 99%
“…However, older adults often mention day-to-day difficulties in remembering everyday events (e.g. Jungwirth, Fischer, Weissgram et al, 2004;Mol, van Boxtel, Willems & Jolles, 2006), and since older adults' community independence and quality of life may depend in part on the ability to remember typical everyday activities, this is an important form of memory that, unusually, remains largely unstudied. The present research, then, examines older and younger adults' memory for everyday events and measures the effect of retrieval support, in the form of SC photographs captured during those events.…”
Section: Introductionmentioning
confidence: 99%
“…Assessments of SMC range from brief questions concerning individuals' perceived memory function or how memory changes may have affected activities of daily living (ADL) (Cook & Marsiske, 2006) to more in-depth questionnaires, such as the Memory Functioning Questionnaire (Gilewski, Zelinski, & Schaie, 1990) or the Metamemory in Adulthood Questionnaire (Dixon, Hultsch, & Hertzog, 1988). SMC are associated with a lower quality of life in older people (Iliffe & Pealing, 2010;Mol, van Boxtel, Willems, & Jolles, 2006). Petersen et al (2001) make a connection between SMC and mild cognitive impairment (MCI) À a concept developed to describe a transitional phase between age-appropriate cognitive functioning and pathological decline .…”
Section: Introductionmentioning
confidence: 99%